Analisis HKSA dan Docking Aktivitas Inhibisi Turunan HEPT terhadap Enzim Reverse Transcriptase HIV (QSAR and Docking of Inhibition Activity of HEPT Derivatives Against Enzym Reverse Transcriptase HIV) - Ani Riani Hasana; Ayik Rosita; Fifteen Aprila Fajrin (Pustaka Kesehatan, 2013)
This study describes the analysis of QSAR and Docking based on the inhibition activity of the enzyme Reverse Transcriptase HIV by 1-[(2-hydroxyethoxy) metil]-6-(phenylthio) timin (HEPT) derivatives. QSAR modeling using 85 compounds HEPT derivatives have calculated the value of biological activity in vitro inhibition of the value of log1/C, then made a linear regression equation against QSAR parameters like as lipophilic, electronic and steric to obtained maximum results correlation r2 by method Multiple Linear Regression (MLR). Docking used to determine the predictive ability of the inhibitor affinity value when HEPT derivatives interacting with the enzyme Reverse Transcriptase HIV. QSAR study results that play a role in the activity is the refractive index parameter (η), molar volume (MV), Parachor (Pc), I2 (parameter which indicates the presence of Sulphur in position R2) and ISP (parameter which indicates the presence of Sulphur in position X). Best equation obtained with compound 75 has a value of R=0.9135, R2adj=0.8064, RMSE=0.5104, and F=69.4881. Docking study results indicate derivatives with the number 80 has the smallest affinity by -11.3 kcal / mol. Keywords: docking, reverse transcriptase enzyme , HEPT, MLR, QSAR.